HUBUNGAN PENERAPAN KONSEP ILMU KIMIA DAN FISIKA PADA PROSES SINTESIS NANOPARTIKEL FE3O4 - Febriliani, Amanda (HINEF : Jurnal Rumpun Ilmu Pendidikan, 2025)
Natural science is one of the branches of science that studies natural phenomena and life around us. The branches of science contained in this natural science include chemistry, physics, biology, geology, and astronomy. Each of these branches of science has a different scope, but overall in general, they are interrelated and complementary sciences in understanding natural phenomena. One example of the application of the interrelationship of these sciences is in the synthesis process of making Fe3O4 nanoparticles. In this synthesis process, the relationship between chemistry and physics is applied. The chemical concepts that occur from this synthesis are the process of chemical reactions and chemical bonds, while the concepts and physical properties that affect during the synthesis process are temperature, magnetism, and homogeneous solutions. Fe3O4 nanoparticles have magnetic properties that are quite strong, the synthesis method used in the manufacture of Fe3O4 nanoparticles is using the coprecipitation method, complemented by testing nanoparticle samples in the form of Vibrating Sample Magnetometer tests. This test, carried out to prove that there is an effect of synthesis temperature on the amount of saturation magnetization contained in Fe3O4 nanoparticles. The results of this study show that nanoparticles with a synthesis temperature of 60°C have a higher saturation magnetization of 59.2 emu / gram compared to the synthesis temperature of 40°C which is 49.5 emu / gram.